MOVBIO - Mobilization of Biomass for Energy Recovery Towards a Sustainable Development - Carvalho, Joana; Mota, André; Ribeiro, André; Soares, Margarida; Araújo, Jorge; Vilarinho, Cândida (European Journal of Sustainable Development, 2018)
The MOVBIO project - Mobilization of pruning biomass for its energy recovery aims at the recovery of existing biomass which, due to its special characteristics, currently does not have a defined use circuit and has no energy use. In particular, by means of the evaluation of the technical and economic feasibility of adaptations in the processes of pretreatment and thermal utilization, it will be facilitated the energetic valorization of pruning biomass of agricultural origin (vines, olive trees, fruit trees) and urban biomass pruning of parks and gardens). The project aims to strengthen the economic model, making it more sustainable through the efficient use of residual biomass and the promotion of business innovation. In order to do so, it is essential to evaluate the real potential for energy recovery of the residual biomass, to make its extraction from the field technically efficient, to characterize as fuel and to adapt the combustion technologies, making them efficient for their final thermal and electrical use. Developing a new management model for this type of biomass will have an impact on companies providing agricultural services, thermal energy consumers, farmers and local governments. The innovative nature of the proposed approach is based on the assessment of the entire value chain, analyzing in detail the characteristics of the selected biomass Keywords: Cross-border Cooperation, Biomass, Energetic Valorization, Spain, Portugal